Dynamic Adjustment in the Heckscher-Ohlin-Samuelson Model - Mussa, Michael (Journal of Political Economy, 1978)
This paper analyzes the dynamic response to a relative price change in a two sector model when the movement of capital from one sector to another requires the use of economic resources. The adjustment process is analyzed as a problem in investment theory; owners of capital balance the costs of capital movement with the expected future benefits. The expectations of capital owners concerning future rental rates in the two industries are shown to play a critical role in determining the efficiency of the adjustment process. When expectations are "rational," the competitive adjustment path maximizes the present discounted value of the economy's final output. When expectations are not rational, the competitive adjustment past is distorted and diverges from the socially optimal path. The paper also analyzes the implications of different assumptions concerning the technology of the adjustment process, establishing that both the adjustment path of the economy and its ultimate long-run equilibrium depend critically on this element of technology.